1997
DOI: 10.1159/000106649
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dementia in German Acute Care Hospitals

Abstract: In this study a representative sample of German acute care hospitals is used to describe the effects of dementia within acute care hospitals. Data from hospital patients above age 60 with the diagnosis dementia (ICD 290, 293, 294 and 310), collected over an observation period of 12 years, are compared with nondemented hospital patients at the same ages. The differences in the average length of stay between demented and nondemented patients are only relatively small in German acute care hospitals. The degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
5
17
0
Order By: Relevance
“…For example, Van Dijk et al [26], examining nursing home residents with unspecified diagnosis of dementia, have reported a greater number of associated diseases than among patients with no or minimal cognitive impairment. Similar evidence was provided by an in-hospital study [27], and among community-dwelling elderly [28]. Comorbidity was found to be higher among patients with dementia, and they were more likely to be diagnosed with congestive heart failure, anemia, and cerebrovascular diseases.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For example, Van Dijk et al [26], examining nursing home residents with unspecified diagnosis of dementia, have reported a greater number of associated diseases than among patients with no or minimal cognitive impairment. Similar evidence was provided by an in-hospital study [27], and among community-dwelling elderly [28]. Comorbidity was found to be higher among patients with dementia, and they were more likely to be diagnosed with congestive heart failure, anemia, and cerebrovascular diseases.…”
Section: Discussionsupporting
confidence: 76%
“…This has been documented among people living in the community [39][40][41], as well as in acute hospital [27] and long-term care settings [39,42], using different instruments for the screening of cognitive impairment. Although estimates of the risk of death among patients with AD have varied greatly, most studies, both institutional [43,44] and community-based studies [45,46], have suggested that it is moderately increased as opposed to unaffected people.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Van Dijk et al [39], examining specifically nursing home residents with dementia, found they had more comorbidity relative to patients less cognitively impaired. In an in-hospital study, comorbidity, rate of infections and mortality were higher among patients with dementia, as opposed to age-matched patients with normal cognitive function [40]. Finally, Callahan et al [41] have reported that community-dwelling elderly with cognitive impairment were more likely to be diagnosed as having congestive heart failure, anemia and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, immune-complex deposits in ANCA-associated glomerulonephritis were shown to be associated with a larger amount of proteinuria, more frequent hypocomplementemia and greater glomerular hypercellularity, with a tendency toward worse renal outcomes [10,11,12]. In patients with typical immune-complex CrGN, such as lupus nephritis and post-streptococcal CrGN, the presence of ANCA has been shown to correlate with more glomerular necrosis and crescent formation [27]. It is postulated that a synergistic effect between ANCA and immune-complex deposition may exist, although the role of glomerular immune-complex deposition in AAV remains unclear.…”
Section: Discussionmentioning
confidence: 99%